2020
DOI: 10.1101/2020.12.04.411934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social network architecture and the tempo of cumulative cultural evolution

Abstract: The ability to build upon previous knowledge—cumulative cultural evolution (CCE)—is a hallmark of human societies. While CCE depends on the interaction between social systems, cognition and the environment, there is increasing evidence that CCE is facilitated by larger and more structured societies. However, the relative importance of social network architecture as an additional factor shaping CCE remains unclear. By simulating innovation and diffusion of cultural traits in populations with stereotyped social … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…having a disproportionate preference for copying a more common behaviour (Aplin et al 2015a)] or if they require passing a certain threshold number of informed contacts before becoming informed (Rosenthal et al 2015). These can modify how transmission pathways emerge from social contacts, and recent studies of how information is accumulated and integrated into cultural traits in structured populations have suggested that transmission properties, rather than contact structure, have the most significant impact on cultural evolution in networks (Cantor et al 2021a). Such findings are highly relevant to the spread of infectious diseases (Sah et al 2017; Evans et al 2020); for example complex parasitic life cycles can impact how social contacts translate to transmission events (Grear et al 2013; Farine 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…having a disproportionate preference for copying a more common behaviour (Aplin et al 2015a)] or if they require passing a certain threshold number of informed contacts before becoming informed (Rosenthal et al 2015). These can modify how transmission pathways emerge from social contacts, and recent studies of how information is accumulated and integrated into cultural traits in structured populations have suggested that transmission properties, rather than contact structure, have the most significant impact on cultural evolution in networks (Cantor et al 2021a). Such findings are highly relevant to the spread of infectious diseases (Sah et al 2017; Evans et al 2020); for example complex parasitic life cycles can impact how social contacts translate to transmission events (Grear et al 2013; Farine 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While social structure, variation in social strategies, and social contact dynamics might be important, studies simulating disease transmission suggest that the importance of social structure in shaping parasite transmission is likely to be over-stated (Sah et al 2017). Recent studies of how information is accumulated and integrated into cultural traits in structured populations have also suggested that transmission properties, rather than contact structure, have the most significant impact on cultural evolution in networks (Cantor et al 2021a). For example, individuals can use different learning rules, such as conformist transmission [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Degree was important to standardize between networks for any comparison, as the probabilities of behaviour acquisition from the NBDA equations are degree dependent. We did not include complete networks, as complete networks are an unrealistic baseline for cultural models [47].…”
Section: Methodsmentioning
confidence: 99%
“…Agents are risk-adverse, seeking higher expected payoffs Agents are risk-neutral, weighing expected payoffs proportionally Agents are risk-tolerant, indifferent to expected payoffs values) but have excluded these from the main text, as the effect of network structure and social transmission on diffusion is a well-explored subject [48,49,50]. The baseline learning rate was set to λ b = 0.05, the social transmission rate was set to s = 5.…”
Section: Agents Linearly Weigh Observed Behavioursmentioning
confidence: 99%
“…one-to-one versus one-to-many) having a greater impact than differences in mechanisms (e.g. indirect cues versus signals) [33]. For example, heart rate matching [34] or signalling a threat to a social partner could have more similar group-level outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%